Avaliação da degradação de corante têxtil por processos fenton e foto-fenton - Torres, Mariana de Almeida (2013)
The present study aimed to evaluate the degradation of textile dye Reactive Black 5 by Fenton and photo-Fenton processes, and evaluate the acute toxicity of the dye before and after treatment, performing tests with Lactuca sativa (lettuce seeds) and Daphnia magna. The degradation studies were performed in conventional photochemical reactor with conditions of iron and hydrogen peroxide previously optimized. Toxicity tests were performed according to the methodology described in the literature. The greatest reduction in the spectral area was observed in the photo- Fenton system (83%), after 60 minutes of reaction. There was also a greater reduction in the concentration of Total Organic Carbon in the samples treated by the photo-Fenton system as compared with the Fenton process. Toxicity tests with Daphnia magna indicated 98,75% immobilization of the organisms in the tests with untreated dye concentrations above 800 mg/L, as well as in samples containing treated dye with pH level around 3 for both processes. It was found a slightly increase in the toxicity after treatment by both Fenton processes in the samples with pH level around 7 for D. magna and L. sativa.